Review of 1971/05/7 Concert at Elgar Concert Room (University of Birmingham). Some Thoughts on the Lunchtime Concert given by the University Improvisation Group - Middleton, Richard (Contact: A Journal for Contemporary Music (1971-1990), 1971)